PEMBERDAYAAN LINGKUNGAN PANTI ASUHAN AISYIYAH MELALUI PELATIHAN PENGELOLAAN LIMBAH SAMPAH PLASTIK DENGAN PEMBUATAN ECOBRIK - Titis Wulandari; Tri Wera Agrita; Agus Fadila Ajis; Oktavian Dwi Prasetyo (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2023)
Garbage is a classic problem that has been a common problem throughout the world, especially in Indonesia. Indonesia as a developing country, the waste problem should receive more attention. One type of waste that should receive more attention is plastic waste. There are many ways to manage plastic waste so that it does not have an impact on the ecosystem. One of the recycling processes that are environmentally friendly and does not cost a lot of money is ecobricks. Ecobricks are the use of environmentally friendly plastic waste that is used as useful items such as chairs or tables. Environmental empowerment of the Aisyiyah Orphanage through training on processing plastic waste with an easy and innovative ecobric making method was carried out on Jl. Cross Sumatra, Bathin III District, Bungo Regency. With the aim of teaching how to make ecobricks in waste reduction only. However, it can also educate plastic waste which is a major environmental problem on earth. Therefore, the Aisyiyah Orphanage became a partner in this activity as a form of movement for a sense of concern for the environment. The service activities were well received by the children in the orphanage, they were super active in participating in the activities. In this activity, the children directly practiced in making ecobricks which made various forms of objects that could be used by children well.